Frolík decompositions for lattice-ordered groups. Issue 3 (3rd April 2018) - Buskes, Gerard; Redfield, R.H.
Abstract: Frolík's theorem says that a homeomorphism from a certain kind of topological space to itself decomposes the space into the clopen set of fixed points together with three clopen sets, each of whose images is disjoint from the original set. Stone's theorem translates this result to a corresponding theorem about the Riesz space of continuous functions on the topological space. We prove a theorem analogous to that for Riesz spaces in the much more general setting of (possibly noncommutative) lattice-ordered groups and group-endomorphisms. The groups to which our result applies satisfy a weak condition, introduced by Abramovich and Kitover, on the polars; the images of our endomorphisms have a kind of order-density on their polars; the double polars of the images are cardinal summands; and the endomorphisms themselves are disjointness-preserving in both directions. We explain how to extend our result to larger groups to which it does not apply, and, to give additional insight, we provide many examples.